Pengembangan e-Presensi Dosen Berbasis Android di Universitas Darul Ulum - Winarti, Winarti; Lisdiyanto, Angga; Abdillah, Ikhwan; Andhyka, Awang Andhykad (Jurnal Sistem Informasi Dan Informatika, 2024)
Lecturer attendance is a crucial element in assessing lecturer performance in higher education institutions. However, the manual attendance methods still widely used have weaknesses, such as the risk of recording errors and fraud. This study aims to develop a QR Code-based lecturer attendance system that can be accessed through Android mobile devices. The system utilizes QR Code technology to ensure real-time and accurate lecturer attendance. The research method used is the waterfall software development model with Unified Modelling Language (UML) modeling. The application is designed using Android Studio and MySQL as the database. The results show that the QR Code-based attendance system can improve the efficiency and accuracy of the lecturer attendance process at the Graduate School of KH. Abdul Chalim Institute, Mojokerto